2021
DOI: 10.3389/fonc.2021.732883
|View full text |Cite
|
Sign up to set email alerts
|

The Sequence of Intracranial Radiotherapy and Systemic Treatment With Tyrosine Kinase Inhibitors for Gene-Driven Non-Small Cell Lung Cancer Brain Metastases in the Targeted Treatment Era: A 10-Year Single-Center Experience

Abstract: PurposeThe high intracranial efficacy of targeted therapeutic agents poses a challenge in determining the optimal sequence of local radiation therapy (RT) and systemic treatment with tyrosine kinase inhibitors (TKIs) in non-small cell lung cancer (NSCLC) patients with brain metastasis (BM). Therefore, we conducted a cohort study to elucidate the appropriate treatment strategy, either upfront RT or deferred RT including a toxicity assessment, in these patients.Patients and MethodsWe retrospectively evaluated pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The majority of brain metastases reported were located at the cerebral hemispheres and cerebellum. Few studies reported the median time interval between the diagnosis of NSCLC and brain metastases; among those studies that did, the average time to diagnosis was between 1 and 2 years (this average does not include patients who had brain metastases at NSCLC diagnosis) [ 45 , 82 , 88 ]. One Japanese retrospective study noted that the rate and frequency of developing brain metastases were rapid and higher in patients with EGFR mutations than in patients without EGFR mutations [ 99 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of brain metastases reported were located at the cerebral hemispheres and cerebellum. Few studies reported the median time interval between the diagnosis of NSCLC and brain metastases; among those studies that did, the average time to diagnosis was between 1 and 2 years (this average does not include patients who had brain metastases at NSCLC diagnosis) [ 45 , 82 , 88 ]. One Japanese retrospective study noted that the rate and frequency of developing brain metastases were rapid and higher in patients with EGFR mutations than in patients without EGFR mutations [ 99 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the first-line setting, treatment with upfront WBRT with or without concomitant TKIs resulted in the more favorable clinical outcomes compared with treatment with TKIs only or upfront TKIs followed by WBRT. Three observational studies found that median CNS-PFS was longer in patients who had received earlier or upfront versus no or delayed radiotherapy [ 32 , 68 , 88 ]. Additional observational studies found that EGFR TKIs in combination or sequenced with radiotherapy (WBRT and/or SRS) had longer median CNS-PFS than with EGFR TKI monotherapy [ 24 , 27 , 30 , 34 , 38 , 82 , 98 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, in a more recent retrospective series of 147 patients either EGFR-mutated (n = 94), ALK-positive (n = 52) or both (n = 1) looking speci cally at the role of SRT in combination with targeted therapies, all treated with CNS-penetrant TKI, the use of an early SRT did not improve PFS or time to intra-cranial progression [24]. In 198 patients with a targetable mutation, Yang [25] compared upfront and deferred radiotherapy (nearly 40% were treated with WBRT): they found that deferred RT had a higher rate of brain progression, with no impact on survival, re ecting again the loss of e cacy of medical treatment to prevent the occurrence of new BM during the course of the disease. In our series, only 17 patients had a targetable mutation, with no difference in local control according to treatment line.…”
Section: Discussionmentioning
confidence: 99%
“…Like our findings, a plethora of research has demonstrated that upfront RT enhances iPFS and OS and increases the rate of BM remission. A retrospective study of 198 eligible patients revealed a significant improvement in iPFS with upfront RT (19.9 vs. 11.1 months, P < 0.001) [ 17 ]. According to Magnuson et al, there were significant differences in OS (46 vs. 30 vs. 25 months, P = 0.001) and iPFS (23 vs. 24 vs. 17 months, p = 0.025) between patients treated with SRS + TKI, WBRT + TKI, or TKI [ 16 ].…”
Section: Discussionmentioning
confidence: 99%